2014
DOI: 10.1002/ejic.201402608
|View full text |Cite
|
Sign up to set email alerts
|

A Pair of Enantiopure Cubane‐Type CuII4O4 Clusters: Synthesis, Structure, Chirality and Magnetism

Abstract: A pair of enantiopure cubane-type Cu II 4 O 4 clusters was constructed from simple chiral ligands (R or S)-2-[(2-hydroxy-1phenylethylimino)methyl]phenol (H 2 L R or S ). Single-crystal X-ray diffraction studies demonstrated that complexes 1R and 1S are enantiomers. They consist of a Cu II 4 O 4 cubane core in which the four Cu II centres are linked by a μ 3 -oxo bridge. The four Cu II ions in one cluster are all in a distorted square-pyramidal geometry. Circular dichroism (CD) spec-[a] Key

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In this work, four types of chiral salicylaldehyde Schiff base ligands with different substituents in the para -position of the salicylaldehyde ring were used to synthesis the series of mixed valence Co II Co III 3 clusters. Our previous work showed that this type of chiral ligands could successfully be employed to construct star-shaped Fe III 4 single-molecule magnets and cubane-type Cu II 4 O 4 clusters . During the synthesis procedure, four different counter cations (H(NEt 3 ) + , H(DIPEA) + , H(DBU) + , and ( n -Bu) 4 N + ) were introduced into the complexes by using different bases (TEA, DIPEA, DBU, and TBAOH) as reaction precursor.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, four types of chiral salicylaldehyde Schiff base ligands with different substituents in the para -position of the salicylaldehyde ring were used to synthesis the series of mixed valence Co II Co III 3 clusters. Our previous work showed that this type of chiral ligands could successfully be employed to construct star-shaped Fe III 4 single-molecule magnets and cubane-type Cu II 4 O 4 clusters . During the synthesis procedure, four different counter cations (H(NEt 3 ) + , H(DIPEA) + , H(DBU) + , and ( n -Bu) 4 N + ) were introduced into the complexes by using different bases (TEA, DIPEA, DBU, and TBAOH) as reaction precursor.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In the study of Fe III 4 series of SMMs, Cornia et al used angular parameters to compare the deviation of coordination sphere from ideal trigonal prism (D 3h ) symmetry. 22 Similarly, the local symmetry of central Co(II) ions in this series of compounds also deviates from ideal D 3h symmetry, to different degrees, so the angular parameters α, β, θ, ϕ, and γ was introduced for benefit of comparison (see Figure 2). The values of α and β can be measured from the crystal structures directly.…”
Section: Synthesis Of [H(netmentioning
confidence: 99%